Indonesian people’s resilience detection method based on big data - Catur Suratnoaji; Irwan Dwi Arianto; Syifa Syarifah Alamiyah (Universitas Padjadjaran, 2022)
The resilience condition of the Indonesian people in facing threats, disturbances, obstacles, and challenges (AGHT) can be identified through conversations on social media. The conversational data of social media users is important data for understanding the national resilience of the Indonesian people. The method developed is more explorative, descriptive, and quantitative by describing the variable: volume of social media users, user profiles, reach, conversation trends, types of issues, top tweets, emotion, sentiment, people who influence (top influencer), intermediary (bridge), and robot analysis (bot analysis). The research sample is from March 1, 2022, to May 1, 2022. Consideration of the timing is due to many public reactions to the “three periods” issue. The results of this study indicate that the three-period issue is the most dominant compared to other topics. The issue of “three periods” spread throughout Indonesia, and the most dominant was in DKI Jakarta Province. The social media users’ profile shows that the issue of three periods is mostly discussed by users between the ages of 19 and 29. Men are more dominant in discussing the “three periods” issue than women. Most Indonesian people reject the three-period issue. It shows that the resilience of the Indonesian people is exceptional because they can confront negative issues.